2016
DOI: 10.1227/neu.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Transsphenoidal Surgery for Cushing Disease

Abstract: Transsphenoidal surgery provides a safe and effective treatment for Cushing disease. For both adults and children, the best outcomes occurred in patients with microadenomas and/or those with type 1 remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
3
33
0
2
Order By: Relevance
“…17 Moreover, they are the second most common nonmalignant brain tumor with surgical resection as a potential curative treatment. While scoring systems have been developed that use radiographic features to classify invasion into adjacent structures 4,10,11 and hormone levels to predict treatment response, 2,25 no scoring system has been developed to comprehensively include patient characteristics and stratify surgical risk. Such scoring systems have been developed for meningiomas, 22 gliomas (both low-grade 3,20 and malignant 13,18 ), brain metastases, 6,7 and arteriovenous malformations 12,23,24 to predict both early and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, they are the second most common nonmalignant brain tumor with surgical resection as a potential curative treatment. While scoring systems have been developed that use radiographic features to classify invasion into adjacent structures 4,10,11 and hormone levels to predict treatment response, 2,25 no scoring system has been developed to comprehensively include patient characteristics and stratify surgical risk. Such scoring systems have been developed for meningiomas, 22 gliomas (both low-grade 3,20 and malignant 13,18 ), brain metastases, 6,7 and arteriovenous malformations 12,23,24 to predict both early and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For patients in immediate remission after surgery, recurrence was considered based on the recurrence symptoms and biochemical evidence of CD, including an elevated morning serum cortisol level or 24-h UFC and a lack of suppression of the morning cortisol after a late evening dose of dexamethasone [12]. MRI, as mentioned above, was also used to confirm recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…33 Remission rates at experienced pituitary centers range between 70% and 90%. 1,6,9,10,11,18,19,24,27,[29][30][31] While many diagnostic tests aid in the localization of ACTH-dependent disease to the pituitary gland (such as ACTH level, pituitary MRI, and inferior petrosal sinus sampling [IPSS]), all of these studies have known weaknesses, and presence of a tumor is not always confirmed. 2 Ultimately, it falls to the discretion of the surgeon on how to manage presumed CD cases when no obvious adenoma is discovered at the time of surgery.…”
mentioning
confidence: 99%